Faktor-faktor Penentu Bagi Pelanggan Bukalapak.com Dalam Memutuskan Pembelian: Citra Perusahaan dan Kualitas Pelayanan - Diah Ernawati (Oikonomia: Jurnal Manajemen, 2022)
The purpose of this study was to examine the factors of corporate image and service quality of Bukalapak.com. in influencing the purchasing decisions of Bukalapak.com customers. Methodology Testing the hypothesis using multiple linear regression analysis with the help of SPSS. Data was collected through distributing questionnaires to 100 respondents by accidental sampling. The findings show that the decision to buy Bukalapak.com customers is determined by the company's image and quality of services provided. Suggestions The quality of service from Bukalapak.com needs to be continuously improved and maintained to be of good quality according to customers. And the company's image needs to be improved continuously through active promotion and socialization. And the selection of stores that are members of Bukalapak also needs to be selected and evaluated strictly to continue to improve the company's good image.